Moderation of Predictor Variables on the Influence of Accountants' Code of Ethics Understanding on Auditors' Ethical Behavior - Juliarsa, Gede; Kresnandra, Anak Agung Ngurah Agung; Sudirga, I Gusti Ayu Desni Saraswati (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to analyze the effect of accountants’ understanding of the code of ethics on auditors’ ethical behavior, considering moderating variables: internal locus of control, emotional intelligence, religiosity, and auditors’ experience. The research population consists of auditors working at Public Accounting Firms (KAP) in Bali Province, selected using purposive sampling. Primary data were obtained through questionnaires tested for validity and reliability. The analysis was conducted using moderated regression analysis (MRA). The results indicate that understanding the code of ethics positively influences auditors’ ethical behavior. Internal locus of control and auditors’ experience do not moderate this influence, whereas emotional intelligence and religiosity strengthen the effect of code of ethics understanding on auditors’ ethical behavior. These findings highlight the importance of enhancing auditors’ emotional and religious aspects to improve ethical behavior.